ANALYSIS OF MATHEMATICS LEARNING AT SMA NEGERI 2 MASOHI - Yosep Tetelepta; Tanwey Gerson Ratumanan; Christin M Laamena (EDU SCIENCES JOURNAL, 2021)
This study aims to analyze the ability of math teachers in learning plan, implementation of learning, and assessment of the learning process in the implementation of the 2013 curriculum. The research was conducted at SMA Negeri 2 Masohi, involving 5 math teachers, namely the first teacher (G1), the second teacher (G2), the third teacher (G3), the fourth teacher (G4), and the fifth teacher (G5). The data was collected by using an assessment of (1) the lesson implementation plan was prepared by each teacher, (2) the learning process was carried out by the five mathematics teachers, and (3) teachers in the assessment process and the learning outcomes of the students. The instruments consist of 3 (three) assessment formats, namely: (1) RPP assessment format, (2) learning assessment format, and (3) learning result assessment format of learners using assessment scale 0 - 4. The results of the study are as follows: (1) The average RPP assessment of the five teachers is 74.40 and fall into the good category (B), (2) The average learning ability score of the five teachers is 80.00 in the good category (B), and (3) The average ability score of the five teachers in carrying out the assessment of the learners' learning outcomes is 80.71 and fall into the good category (B).